EFFECTIVENESS OF PROBLEM-BASED LEARNING IN ENHANCING CRITICAL THINKING SKILLS IN SCIENCE EDUCATION: META-ANALYSIS - Wiratama, Pradeo Putra; Dwandaru, Wipsar Sunu Brams; Kuswanto, Heru; Laeli, Silvia; Kurniawan, Aris (Universitas Labuhanbatu, 2025)
Purpose – As critical thinking is a key competency in science education, this study employs a meta-analysis to systematically evaluate the effectiveness of the Problem-Based Learning (PBL) model in enhancing students' critical thinking skills. This study analyzed 21 articles published between 2017 and 2024. These articles specifically discuss the effectiveness of PBL implementation in enhancing students' critical thinking skills.Methodology – The selection criteria included peer-reviewed articles published between 2017 and 2024, which provided explicit numerical data (sample size, mean, standard deviation) and a direct focus on the impact of PBL on critical thinking skills. A random-effects model was chosen due to expected variability among studies, and the effect size was calculated using Hedges' g to ensure robust findings. Data analysis was performed using SPSS version 29 to calculate the summary effect, analyze heterogeneity, construct a forest plot, and identify potential publication bias.Findings – The meta-analysis revealed a significant improvement in critical thinking skills for students who experienced PBL-based learning compared to conventional methods (summary effect = 0.57, 95% CI = 0.15-1.0, p = 0.01). This shows that 57% of learning with PBL models analyzed has a significant positive effect on students' critical thinking skills. The heterogeneity test indicated (I² value = 93,9% > 25%), suggesting moderate variability among the analyzed studies. Funnel plots and Egger's regression tests indicate no risk of publication bias.Contribution– These findings emphasize the importance of integrating PBL into science curricula to foster critical thinking skills. Educators should consider structured PBL frameworks, while policymakers could support teacher training initiatives to optimize implementation. Future studies may explore longitudinal effects and variations across different educational levels.